Spatiotemporal manipulation of L-arginine release from bioactive hydrogels initiates rapid skin wound healing accompanied with repressed scar formation. (September 2021) - Ling, Zhixin; Deng, Jing; Zhang, Zhuoran; Sui, Heyu; Shi, Wenxiong; Yuan, Bo; Lin, Hai; Yang, Xiao; Cao, Jun; Zhu, Xiangdong; Zhang, Xingdong
Highlights: CA hydrogels with spatial and temporal manipulation of L-Arg release was developed and evaluated. The release profile of L-Arg depended on the substitution degrees of L-Arg on CS. CA2 hydrogel exhibited optimal release kinetics of L-Arg necessary for improving wound healing at different repair stages. The CA hydrogel could enhance the large skin wound healing while reduce scar formation. Abstract: Despite enlarging the promising applications of bioactive hydrogel-based wound dressings, currently designed hydrogels still have the problems of limited capability for large skin wound healing and liable to promote nonfunctioning scar formation. The conundrum is highly due to the random release pattern and spatial distribution of bioactive regulatory cues from the hydrogels at the wound site. To address it, L-arginine (L-Arg) as a bioactive cue was introduced into chitosan (CS) to fabricate biofunctional hydrogel (CA) via a facile synthesizing route in this study, which was firstly applied to unlock the spatial and temporal manipulation of L-Arg release kinetics for regulating the healing process of large full-thickness skin wound. Systematic experiments and molecular dynamic simulations validated that different substitution degrees of L-Arg on CS would influence on their molecular arrangements and interactions significantly, which in turn regulated L-Arg release profiles temporally. In vitro and in vivo studies demonstrated that an optimized hydrogel with 8.50 % substitution degree (CA2) enhanced the wound healing process while reduced scar formation in a 2×2 cm 2 full-thickness skin defect of rat, which could be mainly attributed to the unique L-Arg release profile from CA2 hydrogel in an intrinsically ordered manner during different repair stages. In particular, the relatively more release of L-Arg at the early stage promoted the infiltration and proliferation of various cell types, leading to enhanced angiogenesis and collagen deposition. However, less L-Arg presence at the late stage avoided excessive collagen accumulation and immature blood vessel formation, thus reducing fibrosis scar tissue formation. Overall, the orchestrated process of physiological wound healing would be well-regulated via spatial and temporal control of L-Arg release from CA2 hydrogel, which could be a promising candidate for clinical skin injury repair, particularly large defect. From a material science standpoint, the radical strategy based on rational engineering of polymer structures may extend its application in wound healing.